Stimulus Range and Discontinuity Effects on Information-Integration Category Learning and Generalization - Maddox, W. Todd (2011)
Two studies are reported that support the hypothesis that categories that require a multiple-unit representation, as opposed to a single-unit representation, lead to worse initial acquisition but better generalization. Based on the constraints imposed by the procedural-based learning system thought to mediate information-integration categorization, we argue that the need to train multiple units during initial category acquisition slows the procedural-based category learning process and adversely affects learning performance. However, we speculate that better generalization occurs because of the increased likelihood that a novel stimulus will activate at least one of the multiple units needed to represent the category. Relations to other findings in the literature and the implications of this work for training and clinical assessment are discussed.